MAPPING AND ASSESSING MULTIPLE ECOSYSTEM SERVICES IN AN ALPINE REGION: A STUDY IN TRENTINO, ITALY - Ferrari, M.; Geneletti, D. (Annali di Botanica, 2014)
This research aims to identify ecosystem services relevant for Trentino (a region in the Italian Alps), and to assess them through spatial indicators. 51 experts were involved in the identification of relevant ecosystem services and appropriate indicators to represent them. Indicators were computed using the database available at administrative level. Indicators represent the actual or the potential supply of ecosystem services, expressed in terms of either stock or flow. Moreover, indicators may refer to biophysical, economic or socio-cultural values. In total, the experts selected 25 ecosystem services and 57 assessment indicators. Accordingly, the selected indicators were mapped over different spatial units of ecosystem services representation, including land use and forest types. This research was the first attempt to assess a multiple set of ecosystem services for Trentino. The results provide new information that can be used to achieve the objectives of the EU Biodiversity Strategy by 2014. The proposed approach can be reasonably extended to other Alpine areas with similar morphology, land cover and land use.